2021
DOI: 10.1002/nop2.1059
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular status of breast cancer patients before and after receiving anthracycline chemotherapy regimen

Abstract: Aim To explore the effect of TEC chemotherapy regimen (Docetaxel + Epirubicin + Cyclophosphamide) on traditional cardiovascular risk factors, atherosclerotic cardiovascular disease and cardiac electrical activity. Design 243 patients with first initially diagnosed breast cancer were collected who receiving TEC chemotherapy. Methods Univariate analysis, multivariate analysis, binary logistic regression analysis and statistical description were used to analyse the data. Results Among the first diagnosed patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In another study, 243 patients with newly diagnosed breast cancer received anthracycline and other drugs (Table 1). After chemotherapy, the incidence of hyperlipidemia, level of blood glucose, and prevalence of hyperuricemia was significantly increased, and five patients (2.1%) were diagnosed 10.3389/fcvm.2023.1118002 with coronary artery disease (21). A recent clinical study showed significant increases in the mean carotid intima-media thickness and plaque score in 32 patients who received R-CHOP chemotherapy (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone) for malignant B-cell lymphoma.…”
Section: Chemotherapeutic Drugs 21 Anthracyclinesmentioning
confidence: 99%
“…In another study, 243 patients with newly diagnosed breast cancer received anthracycline and other drugs (Table 1). After chemotherapy, the incidence of hyperlipidemia, level of blood glucose, and prevalence of hyperuricemia was significantly increased, and five patients (2.1%) were diagnosed 10.3389/fcvm.2023.1118002 with coronary artery disease (21). A recent clinical study showed significant increases in the mean carotid intima-media thickness and plaque score in 32 patients who received R-CHOP chemotherapy (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone) for malignant B-cell lymphoma.…”
Section: Chemotherapeutic Drugs 21 Anthracyclinesmentioning
confidence: 99%
“…Radical surgery (Bogach et al, 2022) supplemented by chemotherapy, radiotherapy, endocrine therapy and other therapies (Bhat et al, 2022; Dong et al, 2022; Wang et al, 2020) is the main treatment for BC. Radical surgery for BC primarily includes BC standard radical surgery (Halsted surgery), BC modified radical surgery, simple mastectomy, breast‐conserving surgery, axillary lymph node dissection and sentinel lymph node biopsy (Grebić et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The overall 5-year survival rates of stage I, II and III patients were 98%, 92% and 75% respectively (DeSantis et al, 2019). Therefore, the number of breast cancer survivors will continue to increase.Radical surgery (Bogach et al, 2022) supplemented by chemotherapy, radiotherapy, endocrine therapy and other therapies (Bhat et al, 2022;Dong et al, 2022;Wang et al, 2020) is the main treatment for BC. Radical surgery for BC primarily includes BC standard radical surgery (Halsted surgery), BC modified radical surgery, simple mastectomy, breast-conserving surgery, axillary lymph node dissection…”
mentioning
confidence: 99%